Cinema estrutura: estudo genealógico do cinema estrutural - Stutz, Fernando Henrique Lacerda (2015)
In 1969 the film critic P.A.Sitney said that, suddenly, a cinema structure "had emerged." Although imprecise, his observations were responsible for triggering a long process of discussions about a kind of cinema that, in general, was characterized by self-reflectiveness and antiillusionist processes. The exploration of the filmstrip's materiality, of the alternative projection and camera-capture methods, of the different editing processes and articulation between sound and image, as well as a number of other procedures that called attention to the cinematic structure, were taken as central features of those "structural films." In the search of a genealogical approach of the facts and building on key authors of the genealogical method, especially Nietzsche and Benjamin, alongside with the help of historicaldocumentary data, this research has made clear that the emergence of a dedicated cinematography to its own structure, had derived from a historical development marked by the emancipation of cinema as art, as well as from the development for developing alternatives to the set of cinematic codes agreed by the film industry. From the avant-garde of the 1920s to the artistic movements of the postwar 1950s, the will to acquire an "essential cinematic language have mobilized artists and filmmakers to produce experimental works that questioned such codes, giving rise to the structural films. New York, London and Vienna, altogether saw the development of a filmic production that prioritized to discuss the structural basis of cinematic experience and cinematic discourse from the visual perception phenomena, to cognitive processes during the view. Heterogeneously, the so-called structural works not only cast new light on the film practice itself, expanding its limits; but also demonstrated the possibility of using cinema as an useful instrument for philosophical speculation. Making "films about films", the structural filmmakers completed the avant-garde project of employing film as an autonomous art-form, turning its attention to its own structure, and thereby making the structure of things, the man and his thought more and more visible